Diversity of Colletotrichum species associated with anthracnose on Euonymus japonicus and their sensitivity to fungicides - Liu, Yayong; Tan, Xiaoqian; Zhao, Juan; Niu, Yajie; Hsiang, Tom; Yu, Zhihe; Qin, Wentao (Frontiers in Plant Science, 2024)
As an evergreen shrub, Euonymus japonicus plays a crucial role in urban landscape construction, and its growth is affected by severe foliar anthracnose caused by Colletotrichum spp. However, the biodiversity of Colletotrichum species associated with anthracnose on E. japonicus remains undetermined. This study involved a two-year collection of E. japonicus leaf samples with typical anthracnose symptoms from 9 districts in Beijing, China. A total of 194 Colletotrichum isolates were obtained, and eight Colletotrichum species were subsequently identified using morphological characteristics and molecular identification with the ACT, GADPH, CHS, TUB2, and CAL genes, as well as the rDNA-ITS region. These species included Colletotrichum aenigma, C. fructicola, C. gloeosporioides, C. grossum, C. hebeiense, C. karstii, C. siamense, and C. theobromicola with C. siamense being the most prevalent (57%), followed by C. aenigma and C. theobromicola. Furthermore, C. fructicola, C. grossum and C. hebeiense are reported for the first time as causal agents of anthracnose on E. japonicus worldwide, and C. karstii is newly reported to be associated with E. japonicus anthracnose in China. Pathogenicity tests revealed that all tested isolates exhibited pathogenicity in the presence of wounds, emphasizing the need to avoid artificial or mechanical wounds to prevent infection in E. japonicus management. The EC50 values of five fungicides, namely difenoconazole, flusilazole, tebuconazole, hexaconazole, and prochloraz, were found to be less than 10 mg/L, indicating their strong potential for application. Notably, the EC50 of prochloraz was less than 0.05 mg/L for C. theobromicola. These findings offer valuable insights for the management of anthracnose on E. japonicus.